2016
DOI: 10.1542/peds.2015-1313
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D: A New Promising Therapy for Congenital Ichthyosis

Abstract: Severe vitamin D deficiency and rickets are highly prevalent among children with congenital ichthyosis. We report an incidental observation of a dramatic and excellent clinical response with regard to skin scaling and stiffness in children with congenital ichthyosis after short-term high-dose vitamin D supplementation that has not been previously described. Seven children with congenital ichthyosis (5 with autosomal recessive congenital ichthyosis; 2 with epidermolytic ichthyosis) and severe vitamin D deficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 13 publications
(9 reference statements)
1
24
0
4
Order By: Relevance
“…Modified stoss therapy in which 60,000 IU of oral cholecalciferol was given daily for 10 days was tried by Sethuraman et al in our institution which gave promising results in severe clinical rickets and congenital ichthyosis. 27 In the present study, we supplemented single megadose oral vitD at 10,000 IU/kg, 2 ± 1 weeks prior to elective ICR in pediatric CCHD patients with TOF. Sheperd et al in a retrospective review, identified the role of administering stoss therapy for effectively treating severe vitD deficiency in cystic fibrosis children.…”
Section: Discussionmentioning
confidence: 99%
“…Modified stoss therapy in which 60,000 IU of oral cholecalciferol was given daily for 10 days was tried by Sethuraman et al in our institution which gave promising results in severe clinical rickets and congenital ichthyosis. 27 In the present study, we supplemented single megadose oral vitD at 10,000 IU/kg, 2 ± 1 weeks prior to elective ICR in pediatric CCHD patients with TOF. Sheperd et al in a retrospective review, identified the role of administering stoss therapy for effectively treating severe vitD deficiency in cystic fibrosis children.…”
Section: Discussionmentioning
confidence: 99%
“…Although no curative therapy exists for ichthyoses to date, there are a few approaches in terms of topical applications. 46,[58][59][60] An example for a successful treatment of ichthyosis symptoms is a combined therapy with lovastatin (statin drug) and cholesterol for persons with congenital hemidysplasia with ichthyosiform erythroderma syndrome (CHILD [MIM: 308050]), an X-linked dominant cholesterol metabolic disorder caused by mutations in NSDHL (MIM: 300275). 61 It is conceivable that treatment with cholesterol sulfate, the end product of the conversion catalyzed by SULT2B1, might enable the correct procession of lamellar bodies and consequently improve the phenotype of SULT2B1-deficient persons.…”
Section: Discussionmentioning
confidence: 99%
“…The risk for 25‐hydroxyvitamin D deficiency in CI is well established, especially in children, with many case reports in the literature. These include four small retrospective series of five to 15 patients with keratinization disorders, including CI, and three prospective studies of 45–119 patients with CI . The underlying mechanism of vitamin D deficiency in CI remains unclear.…”
Section: Complicationsmentioning
confidence: 99%